Forced convective condensation flow and heat transfer characteristics of hydrocarbon mixtures refrigerant in helically coiled tubes. (September 2018) - Yu, Jiawen; Jiang, Yiqiang; Cai, Weihua; Li, Fengzhi
Highlights: A numerical model was established to study the condensation heat transfer characteristics. Flow condensation heat transfer characteristics were analyzed. The effect of different structural parameters on heat transfer characteristic was studied. Regimes were observed by the simulation, and a new flow regime transitional line was proposed. Flow patterns in the helical tube were observed. Abstract: Helical tube has been widely used in liquefied natural gas (LNG) liquefying applications. However, studies on the heat transfer performance of hydrocarbon mixture refrigerant in a helical tube have rarely been conducted. In this paper, condensation heat transfer characteristics of hydrocarbon mixture refrigerant in a helical tube were investigated numerically. The tests were conducted at saturation pressure of 2–4 MPa, mass flux of 100–400 kg/(m 2 ·s) and vapor quality 0–1. The numerical model was well verified by experimental data. And the effects of different structural parameters (tube diameter, helix angle and curvature diameter) and operating parameters (mass flux, heat flux and saturation pressure) on the heat transfer of hydrocarbons refrigeration were considered. The results showed that the tube diameter and mass flux had significant effect on condensation heat transfer coefficient. Meanwhile, stratified flow, half-annular flow and annular flow were observed during the condensation of methane/propane mixtures refrigerant by simulations, and a new flow pattern transition line for hydrocarbon refrigerants condensation process was proposed. Finally, the simulation results were compared with several well-known condensation heat transfer correlations. The research results will provide some constructive instructions for more effective design of LNG heat exchanger.